Conflict Between Health Law and Territorial Quarantine Law Regarding the Provision of COVID-19 Vaccine - Yazid Bustomi (Universitas Negeri Semarang, 2021)
In the context of preventing the increasingly widespread Covid-19 which has claimed many lives, the Indonesian government has made various efforts to overcome this and the most recent effort is giving Covid-19 vaccinations to the public. In practice, various conflicts emerge and one of them is the conflict between Law Number 6 of 2018 concerning Health Quarantine which states that vaccines are an obligation and Law Number 36 of 2009 concerning Health which states that vaccines are a right. This type of research is juridical normative using a statutory and conceptual approach. The results of this study indicate that Covid-19 is an emergency so that the principle of non-habet legem necessity applies, which means that in a state of legal emergency it does not apply, so that regulatory conflicts regarding Covid-19 vaccination do not become a problem, because the current government's efforts are the safety of the people. the highest law in an emergency, this is also in line with the salus populi suprema et lex principle. To ensure the safety of the people, the government is obliged to make efforts to vaccinate Covid-19 to restore the situation to its original state, this is in line with the principle of restutio in integrum. In its enforcement, sanctions are needed to make the community obey. However, several regulations have different norms regarding sanctions for those who do not comply and until now there have been no specific regulations from the center regarding the provision of the Covid-19 vaccine. As a conclusion, currently giving the Covid-19 vaccine is mandatory because it is an emergency, but the government also needs to make special regulations from the center regarding vaccine administration regulations so that there are no disparities between each of the regulations from the vaccine-giving regions.